Effect of Phobia Disorders on Emotional Early Childhood - Nur Hazizah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This article aims to determine parental understanding of the development of emotional problems in children who have a phobia disorder and know how to overcome the phobia. Knowing what emotions occur due to phobia. And what methods are used by parents in overcoming the phobia. In general, emotions are divided into two, namely positive emotions and negative emotions. Phobia in children is a form of negative emotion. The phobia where children have excessive fear or anxiety. Emotional children will be disrupted due to the phobia they experienced. Phobias can be lost by providing stimulation from an early age.Keywords: Emotional, Phobia Disorders